INFORMATION SYSTEM AUDIT ON IT GOVERNANCE USING COBIT REFERENCE MODEL APPROACH - fahrizal wahyudi, fahrizal wahyudi (TEKNOFILE : Jurnal Sistem Informasi, 2025)
Information system audits play an important role in ensuring the effectiveness of information technology governance (IT Governance) within an organization. This study aims to evaluate the suitability of information system management with IT governance principles using the COBIT (Control Objectives for Information and Related Technology) reference model approach. The main issues raised include low IT process efficiency, weak internal control, and less than optimal achievement of IT strategic objectives. This study uses a case study method with a qualitative descriptive approach, which is applied to a higher education institution. Data collection was carried out through interviews, observations, and internal document analysis, then evaluated using domains and processes in the COBIT 5 framework, especially in the EDM (Evaluate, Direct and Monitor) and MEA (Monitor, Evaluate and Assess) areas. The results of the study indicate that the capability level of several IT processes is still at level 2 (managed), which means that management has been carried out but has not been optimally documented and is inconsistent. Recommendations for improvement are focused on improving documentation, routine monitoring, and integration between IT policies and the institution's strategic objectives. These findings indicate that the use of COBIT as an audit tool is able to provide an objective picture of the existing IT governance conditions.